Web-Based Financial Ratio Application Program Design for Facilitating MSMEs in Managing Business Finances in the Digital Era - Tino Kemal Fattah; Putriana Salman; Muhammad Syahid Pebriadi; Ningtyas Rahmawati (Cita Konsultindo Research Center, 2023)
This research aims to design a web-based Financial Ratio Application Program to facilitate Small and Medium-sized Enterprises (UMKM) in managing their business finances in the digital era using Extreme Programming. In the context of existing research, traditional financial management methods are no longer sufficient for UMKM's needs in the digital age. Therefore, this study employs Extreme Programming as the research method, which ensures rapid development, flexibility, and customer-centricity. The main results of this research demonstrate a novel contribution by providing an innovative web application that empowers UMKM owners to efficiently calculate and analyze financial ratios, aiding them in making informed financial decisions. This application offers an intuitive user interface, real-time data updates, and customizable features tailored to UMKM requirements, ultimately enhancing their financial management capabilities. Keywords: Financial Ratio Application, Web-based, UMKM, Digital Era, Extreme Programming.